A Systematic Library Review on the Role of English-Language Films in Enhancing Vocabulary Acquisition Among Generation Z EFL Learners - Lafifatul Hafizah; Athifah Hilwa Taqiyya; Salsabila Putri Dzakira; Wahyu Indah Mala Rohmana (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2025)
This study examines the use of English-language films as a medium for improving vocabulary acquisition among Generation Z learners in English as a Foreign Language (EFL) setting. As digital-native learners who favor visual and interactive input, Gen Z often finds conventional vocabulary instruction less engaging. Films provide authentic dialogue, contextual cues, and subtitles that support lexical retention and meaningful comprehension. Using a qualitative library-based approach, this research reviewed 10 studies published between 2015 and 2025 and analyzed them through thematic content analysis. The review highlights several recurring findings: films enhance vocabulary retention through contextual exposure, subtitles strengthen lexical awareness, and audiovisual input increases learner motivation. Subtitled films are shown to improve both receptive and productive vocabulary, especially when paired with active learning strategies such as note-taking and group work. Evidence from Indonesian EFL contexts also shows gains in lexical fluency and pragmatic ability. Overall, films offer a more engaging alternative to rote memorization and align well with Gen Z learning habits. The study recommends integrating film-based tasks into classroom practice to support communicative competence, digital literacy, and broader cultural understanding.